Effects of network structures on the tensile toughness of copper-catalyzed azide-alkyne cycloaddition (CuAAC)-based photopolymers - Song, Han Byul (Macromolecules, 2021)
In the present study, the photo-initiated copper-catalyzed azide-alkyne cycloaddition (CuAAC) polymerization was utilized to form structurally diverse glassy polymer networks. Systematic alterations in the monomer backbone rigidity (e.g., cyclic or aliphatic groups with a different length of backbone) and the reactive functional group density (e.g., tetra-, tri-, di-, and mono-functional azide and alkyne monomers) were used to provide readily tailorable network structures with crosslink densities (estimated from the rubbery modulus) varying by a factor of over 20. All eight of the resultant networks exhibited glass transition temperatures (T(g)) between 50 and 80 °C with tensile toughness ranging from 28 to 61 MJ m(−3). A nearly linear dependence of yield stress and elongation at break (broadly defined as strength and ductility, respectively) on the T(g) and rubbery modulus was established in these triazole networks. When a flexible di-alkyne monomer (5 carbon spacing between alkynes) was incorporated in a network composed of a tri-alkyne and di-azide monomer, the elongation at break was improved from 166 to 300 %, while the yield stress was reduced from 36 to 23 MPa. Additionally, the polymer ductility was also varied by incorporating mono-functional azides as chain ends in the network - replacing a sterically hindered stiff mono-azide with a more flexible mono-azide increased the elongation at break from 24 to 185 % and the tensile toughness from 6 to 28 MJ m(−3).